The machine is an allagmatic being: Epistemic contributions to the posthuman sciences from the philosophy of Simondonian individuation - Feruglio Ortiz, Hector Ariel (2025)
This era is characterized by a great epistemic mutation that emerges from a redefinition of the link between the human, the technical and the living. These mutations allowed the emergence of new discursive formations organized from an infocommunicative background. Within this new order of knowledge, the notion of machine emerges as an epistemic figure with great heuristic potential. Our work is aimed at specifying the scope of this figure as a paradigm of intelligibility based on the contributions of Gilbert Simondon. To achieve this purpose, we will describe the individuation process from a Simondonian perspective to present an epistemological technology aimed at the formation of new paradigms. We consider that proposing the machine as an allagmatic being offers us a reflective technology that can contribute significantly to the epistemic conformation of the posthuman sciences.